Creative edutainment virtual museum application for Lembah Bujang using exploratory approach - Fong, Yin Dee (2023)
Because of the rapid advancement of technology and the impact of COVID-19, the trend of users' and companies' preferences for working and studying remotely has shifted dramatically today. As a result, the use of remote access and telecommunication technologies has skyrocketed, with numerous societal benefits. Asa result, the digital transformation is affecting and gradually replacing traditional business and management models. especially for museums that had faced a massive decline in visitors due to the pandemic. Therefore, this project is conducted to help Lembah Bujang Archaeological Museum undergo digitalization by studying the usageof multimedia technology to assist users in learning, creating an interactive 3D environment-based Virtual Museum application that is more educative and interesting for an exploratory approach, and identifying its effectiveness to act as an assisting tool in the education field. In addition, there will be a total of 5 scopes while designingthe system, which are the Virtual Tour, Gallery, Screen Capture, History Corridors, and Floor and Map Navigation modules. As for the methodology, the Addie model will be used throughout the whole project because it is a very effective tool to facilitatethe analyze, design, develop, implement, and evaluate process and can help deliver the outcome at a higher standard. To conclude, there is a wide variety of tools needed to develop the project, which are the hardware and different types of software that are essential and important, including the text, graphic, audio, video, animation, and authoring editing software.